A Model for Planning Ambulatory Health Services - Ittig, Peter T. (Management Science, 1978)
This paper reports results of a study that develops improved methods of planning ambulatory health services for a specified population. Some of the difficulties of the problem are discussed and a linear model is presented that aids the planning process by accounting for a wide range of data on the population, finances, and system dynamics. Sample results are shown and some implications for further research are discussed.